2020
DOI: 10.3389/fpls.2020.589517
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Genome Editing Technology: A Valuable Tool for Understanding Plant Cell Wall Biosynthesis and Function

Abstract: For the past 5 years, clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) technology has appeared in the molecular biology research spotlight. As a game-changing player in genome editing, CRISPR/Cas9 technology has revolutionized animal research, including medical research and human gene therapy as well as plant science research, particularly for crop improvement. One of the most common applications of CRISPR/Cas9 is to generate genetic knock-out mutants. Recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 137 publications
(184 reference statements)
0
25
0
Order By: Relevance
“…Consequently, the GTs responsible for adding the sugars to AGPs are of particular interest. Studying these GTs can be particularly challenging for several reasons, including the finding that these GTs exist in gene families and have overlapping and redundant activities, which makes it difficult to examine their effects on AGP structure and function [26,27]. showed a delayed germination phenotype.…”
Section: Crispr-cas9 Gene Editing Facilitates Study Of Gts Involved Imentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the GTs responsible for adding the sugars to AGPs are of particular interest. Studying these GTs can be particularly challenging for several reasons, including the finding that these GTs exist in gene families and have overlapping and redundant activities, which makes it difficult to examine their effects on AGP structure and function [26,27]. showed a delayed germination phenotype.…”
Section: Crispr-cas9 Gene Editing Facilitates Study Of Gts Involved Imentioning
confidence: 99%
“…Yariv treated Arabidopsis roots exhibit a short, swollen root phenotype, which is caused by an inhibition of cell proliferation and cell elongation [23]. Several other AGP-related GTs or AGP mutants such as reb1-1, ray1, fut4/fut6, glcat14a-1, fla1, fla4/sos5 and agp30, also display abnormal root phenotypes under normal or salt-stress conditions in Arabidopsis [12][13][14][26][27][28][29]. In addition, AGPs antibodies such as JIM8, JIM13, and LM2 localize AGPs in primary roots, root caps, and root hairs [30][31][32].…”
Section: Agp Glycosylation Contributes To Normal Root Growth In Arabimentioning
confidence: 99%
“…In general, the development of synthetic biotechnology provides new opportunities for the construction of vitamin cell factories. First, high-throughput screening of high-yield strains, the CRISPR/Cas9 genome editing technology, and automatic gene assembly technology provide important technical means for the mining and genetic modification of chassis cells (Chang et al, 2019;Zeng W. et al, 2020;Zhang and Showalter, 2020). Further, the output of vitamin products in different dimensions will be increased by transforming the complex and multi-enzyme pathways required for the production of vitamins, establishing microbial flora with controllable functions and stability, and application of some advanced engineering technology, such as the cold-shock-triggered temperature control system, dynamic control of gene expression systems, different types of biosensors, cell-free systems and computer-aided design, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the CRISPR/ Cas9 system may provide an insight into the genetic control of the structure and functions of plant cell wall (Whitehead et al, 2018;Cao et al, 2020;McCarty et al, 2020). At present, these methods are generally used in studies focusing on cell wall synthesis pathways (including enzymes) and analyzing the exact functions of cell wall elements (Zhang and Showalter, 2020) for the improvement of crop products Wang D. et al, 2019). However, Makarova et al (2018) indicated the application of the CRISPR/Cas9 system for generating plant resistance (not precisely associated with cell wall) against various pathogens.…”
Section: Future Prospectsmentioning
confidence: 99%